2017
DOI: 10.3389/fnmol.2017.00090
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis of Microglia Reveals Time-Dependent Activation of Specific Genetic Programs following Spinal Cord Injury

Abstract: Neurons have inherent competence to regrow following injury, although not spontaneously. Spinal cord injury (SCI) induces a pronounced neuroinflammation driven by resident microglia and infiltrating peripheral macrophages. Microglia are the first reactive glial population after SCI and participate in recruitment of monocyte-derived macrophages to the lesion site. Both positive and negative influence of microglia and macrophages on axonal regeneration had been reported after SCI, raising the issue whether their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 78 publications
5
91
0
Order By: Relevance
“…Table shows some features of aberrant glial cells, including astrocytes or microglia, abnormally‐expressing markers from different cell lineages have been also reported in Alzheimer's disease, Huntington's disease, central nervous system acute lesions and aging, as well as glioma, brain ischemia and trauma, further suggesting the phenotypic switch is strongly associated with inflammation and tissue remodeling after damage.…”
Section: Phenotypic Heterogeneity Of Astrocytes In Als and Other Neurmentioning
confidence: 80%
See 1 more Smart Citation
“…Table shows some features of aberrant glial cells, including astrocytes or microglia, abnormally‐expressing markers from different cell lineages have been also reported in Alzheimer's disease, Huntington's disease, central nervous system acute lesions and aging, as well as glioma, brain ischemia and trauma, further suggesting the phenotypic switch is strongly associated with inflammation and tissue remodeling after damage.…”
Section: Phenotypic Heterogeneity Of Astrocytes In Als and Other Neurmentioning
confidence: 80%
“…expressing markers from different cell lineages have been also reported in Alzheimer's disease, 75 Huntington's disease, 76 central nervous system acute lesions [77][78][79] and aging, 74,80 as well as glioma, 56,57,81 brain ischemia and trauma, 78,79,82 further suggesting the phenotypic switch is strongly associated with inflammation and tissue remodeling after damage. Compared with microglia/macrophages, astrocytes have been regarded to retain fewer phagocytic abilities.…”
Section: Phenotypic Heterogeneity Of Astrocytes In Als and Other Neurmentioning
confidence: 86%
“…In a study of facial nucleus axotomy, the authors also related the observed microglial phenotype (134) to the DAM phenotype, as well as to a phenotype found in the Ck-p25 model (109): 72 genes were regulated in common between all three studies representing almost 75% of all genes upregulated in the facial nucleus axotomy model. Interestingly, in an SCI transcriptomic study, a profile of microglia reminiscent of the CD11c+ phenotype was identified (with upregulation of Gpnmb, Spp1, Lpl, Apoe, Igf1, Lgals3, and Itgax among others) and persisted in a full transection model, whereas it contracted concomitantly to recovery in a hemisection model (135), indicative of the transitory nature of this subset. Conversely, in TBI, the microglial signature was further from the CD11c+ microglia signature, although Itgax was among the upregulated genes 14 and 60 days post-injury, possibly indicating once again a dilution of the signature in all microglia (136).…”
Section: Stroke Ischemia and Injurymentioning
confidence: 99%
“…As the brain develops, immature microglial cells differentiate as they continue a complex lifelong interplay with neuronal cells, downregulating signal pathways such as C-X-X motif chemokine ligand 12 (CXCL12) and C-X-X motif chemokine receptor 4 (CXCR4), and upregulating others [48], to become mature microglia. RNA sequence analysis has provided novel insights into the plasticity of microglia in models of neurodegeneration (e.g., inducing facial nerve axotomy in mice) or inflammation (e.g., inducing spinal cord injury in non-human primate models) [49][50][51]. For instance, an established unique set of genes that are preferentially expressed by aging microglia were found to be enriched in pathologies such as Alzheimer's disease or multiple sclerosis [49].…”
Section: The Developing Brain As a Unique Tumor Sitementioning
confidence: 99%